2019
DOI: 10.1001/jamapsychiatry.2018.4126
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Schizophrenia-Risk Nonsynonymous Variant With Putamen Volume in Adolescents

Abstract: Key Points Question Is there any genetic variant associated with adolescent brain development that can inform psychopathology of schizophrenia? Findings In this imaging genetics study of brain structure, a significant association between a missense mutation in SLC39A8 (a gene previously associated with schizophrenia) and gray matter volume in putamen was discovered and replicated using 10 411 healthy participants from 5 independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 72 publications
(131 reference statements)
2
49
0
Order By: Relevance
“…Though our sample size is smaller than prior studies (8,29), a preliminary analysis using FreeSurfer software (http://surfer.nmr.mgh.harvard.edu/) showed no detectable difference in volume between genotypes in any brain region, suggesting that MRI signal changes in A391T carriers likely result from differences in the concentrations of paramagnetic ions such as Mn (data not shown). ANOVA analyses each element showed that only Mn was statistically different between genotypes (F = 6.472, p = 0.0022, DF = 2).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Though our sample size is smaller than prior studies (8,29), a preliminary analysis using FreeSurfer software (http://surfer.nmr.mgh.harvard.edu/) showed no detectable difference in volume between genotypes in any brain region, suggesting that MRI signal changes in A391T carriers likely result from differences in the concentrations of paramagnetic ions such as Mn (data not shown). ANOVA analyses each element showed that only Mn was statistically different between genotypes (F = 6.472, p = 0.0022, DF = 2).…”
Section: Resultsmentioning
confidence: 79%
“…Previous studies have linked the rs13107325 minor allele (T) with brain MRI changes attributed to regional volumetric differences (8,29). Given the paramagnetic properties of Mn and its known effect on MRI relaxation time (30)(31)(32), we hypothesized that the signal change resulted from changes in local concentrations of Mn and related ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we went on to test whether such an association was tissue specific and whether this SNP had cis-regulations on expressions of the nearby genes. For this extended exploration, we corrected for multiple comparisons between the number of nearby genes and the number of brain areas 22 . Considering the limited sample size in the UKBEC database, we also explored the Genotype Tissue Expression project (GTEx V8, including 17,382 RNA-Seq samples from 948 donors) 43,44 .…”
Section: Association Of Rs2535629 and Rs3617 With Expression Level Ofmentioning
confidence: 99%
“…This irreproducibility can significantly hamper the reliability of the identified disease signature and restrict the clinical application of the discovered DEGs . Moreover, this may be the reason why there is no objective molecular marker available for the diagnosis or treatment of SZ, and why the cause of SZ remains a profound mystery in the community of biomedical researches …”
Section: Introductionmentioning
confidence: 99%